2007
DOI: 10.1080/15376510601003769
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Phosphodiesterase-5 Inhibitor in Experimental Inflammatory Bowel Disease; Molecular Evidence for Involvement of Oxidative Stress

Abstract: Inflammatory bowel disease (IBD) is a common and chronic gastrointestinal disorder characterized by intestinal inflammation and mucosal tissue damage. Reactive oxygen metabolites (ROMs) play a pathogenic role in IBD. We aimed to examine the protective effect of sildenafil, a cGMP phosphodiesterase inhibitor, in the experimental mouse model of IBD. Intrarectal instillation of acetic acid was used to induce IBD. Prednisolone was used as the standard drug for comparison. Sildenafil was used at doses of 0.75, 1.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 52 publications
3
19
0
1
Order By: Relevance
“…It has been suggested that control of oxidative stress in IBD may attenuate biochemical and histopathological variables of IBD [8][9][10][11]. In this regard, existence of oxidative stress in biological fluids such as saliva [12], plasma [13], and colonic mucosal biopsies [2] of subjects with IBD has been already confirmed.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…It has been suggested that control of oxidative stress in IBD may attenuate biochemical and histopathological variables of IBD [8][9][10][11]. In this regard, existence of oxidative stress in biological fluids such as saliva [12], plasma [13], and colonic mucosal biopsies [2] of subjects with IBD has been already confirmed.…”
Section: Introductionmentioning
confidence: 82%
“…A long piece of colon (5 cm) was flushed gently with saline, cut open and maintained at -20ºC. To measure biochemical biomarkers, the colonic samples were minced on ice and homogenized in 10 mL of ice cold 50 mM potassium phosphate buffer (pH 6.0), containing 0.5% HETAB and 10 mM EDTA [8][9][10][11]. The homogenates were then sonicated and centrifuged for 20 min at 12000 g and the supernatant was transformed into several microtubes for separate biochemical assays and frozen at -20ºC until analysis.…”
Section: Induction Of Colitis and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since endothelial dysfunction plays a key role in the pathogenesis of the atherosclerotic process, grow ing interest in the effects of PDE5i in preventing atherosclerosis and the vascular endothelium damage has developed [21] . The event that triggers endothelial dysfunction is represented by the reduction of overall antioxidant pool with the consequent reduced response to oxidative stress and the activation of several pro atherogenic processes [22] (Table 3): (1) reduction of NO bioavailability; (2) increased levels of circulating free fatty acids with subsequent subendothelial storage of lipid depots; and (3) increased smooth muscle cell proliferation of the media layer of the vascular wall [23] . Proinflammatory and infective processes may in turn contribute to activate and amplify the acute endothelial injury, thus perpetuating a vicious circle.…”
Section: Inhibitorsmentioning
confidence: 99%
“…92 On the other hand, the antiphosphodiesterase activity of flavonoids could raise intracellular cyclic adenosine monophosphate and cyclic guanosine monophosphate levels. 93 The elevation of these levels is involved in reducing oxidative stress, 72,[94][95][96][97][98][99] suppressing secretion of tumor necrosis factora, and inhibiting production of superoxide anions. 100,101 Tumor necrosis factor-a is an adipokine related to inflammation induction and is a key mechanism of disease.…”
mentioning
confidence: 99%